(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the quality of life of patients before and after anorectal surgery at Vinmec Times City International Hospital in 2025. Subjects and methods: A cross-sectional descriptive study was conducted from January to June 2025, involving 106 patients who underwent anorectal surgery. A convenience sampling method was applied. Data were collected at two time points (before surgery and 1 month postoperatively) by the face-to-face interviews using the SF-36 questionnaire and to be assessed as higher scores as better quality of life. Data were processed and analyzed using SPSS version 20.0. Results: The patient’s quality of life improved significantly after anorectal surgery. Before surgery, most patients had a moderate or poor quality of life, with a mean score of 53.09 ± 14.93. After surgery, the mean score increased to 82.87 ± 6.71, and 84.9% of patients reported good or excellent quality of life. The improvement was statistically significant across all domains of the SF-36 scale (p < 0.001), with the most notable gains observed in physical functioning, role limitations, pain control, emotional well-being, and vitality. Conclusion: Anorectal surgery significantly improves patients’ quality of life, with marked increases in both mean scores and the proportion of individuals reporting good or excellent is 84,9% after surgery.